KEY CONCEPTS AND TERMINOLOGY OF THE EMERGING MARKET ECONOMY - Khayrullayeva, Nodira; Nematova , Rukhshon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
The gap in economic development between developed and developing economies has actualized the study of the concepts, causes, and factors of this phenomenon. Although developed economies demonstrate a high GDP per capita, emerging market are growing at a faster rate. Emerging markets are countries with market economies and possess institutions and standards inherent in developed countries. However, the maturity and quality of these institutions do not fully comply with those in developed countries. Meanwhile, the economic growth rates of emerging markets are significantly higher than those of developed markets. This study analyzes emerging markets and the problem of their income gap compared to developed countries from various economic study analyzes emerging markets and the problem of their income gap compared to developed countries from various economic approaches, including classical mercantilism, liberalism, Marxism, and modern-dependency theory. In addition, the authors analyzed the role of globalization, its impact on emerging markets, and the causes of economic instability and development. Furthermore, the study considers general trends inherent in developed and developing countries and specific ones’ characteristic only for emerging markets.